Ethnobotanical Knowledge of Magar Community in Siluwa VDC, Palpa District, Nepal - Ale, Rita; Raskoti, Bhakta Bahadur; Shrestha, Keshav (Journal of Natural History Museum, 2009)
Ethnobotanical knowledge, associated with plant resources was studied in Siluwa village development committee, Palpa district. Rapid rural appraisal tool was used to obtain information of indigenous people. This study revealed that Magar community has a vast knowledge of using plant resources. Local people are using plants for medicinal, wild fruit, food, religious and other various domestic purposes. The ethnobotanical knowledge is gradually decreasing in the younger generations. Key words: Indigenous knowledge; use of plants; Magar community. Journal of Natural History Museum Vol. 24, 2009 Page: 58-71